2023
DOI: 10.3847/1538-4357/ad02fb
|View full text |Cite
|
Sign up to set email alerts
|

All-sky Kinematics and Chemistry of Monoceros Stellar Overdensity

Lais Borbolato,
Hélio D. Perottoni,
Silvia Rossi
et al.

Abstract: We explore the kinematic and chemical properties of the Monoceros stellar overdensity by combining data from the Two Micron All Sky Survey, Wide-field Infrared Survey Explorer, APOGEE, and Gaia. Monoceros is a structure located toward the Galactic anticenter and close to the disk. We have identified that its stars have azimuthal velocity in the range of 200 < v ϕ (km s−1) < 250. Combining their kinematics and spatial distribution, we designed a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
1
0
0
Order By: Relevance
“…To further investigate if ACS and MNC share the same star formation history and thus the same chemical patterns as the Galactic thin disk, we definitely need to explore more elements. Toward this, Chou et al (2010) measured the Ti, Y, and La abundances of MNC and argued their chemical trajectories agree with the trends outlined by Galactic stars, and a recent work showed similar results in Mg, Al and Ni abundances (Borbolato et al 2024). Our work gives a more complete picture to this investigation: we have confirmed that ACS and MNC are dynamically consistent with the Galactic thin disk.…”
Section: Chemodynamical Signaturessupporting
confidence: 80%
“…To further investigate if ACS and MNC share the same star formation history and thus the same chemical patterns as the Galactic thin disk, we definitely need to explore more elements. Toward this, Chou et al (2010) measured the Ti, Y, and La abundances of MNC and argued their chemical trajectories agree with the trends outlined by Galactic stars, and a recent work showed similar results in Mg, Al and Ni abundances (Borbolato et al 2024). Our work gives a more complete picture to this investigation: we have confirmed that ACS and MNC are dynamically consistent with the Galactic thin disk.…”
Section: Chemodynamical Signaturessupporting
confidence: 80%